2018
DOI: 10.1002/anie.201712167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stereochemical Revision of the C31–C67 Fragment of Amphidinol 3

Abstract: Amphidinol 3 (AM3) is a marine natural product produced by the dinoflagellate Amphidinium klebsii. Although the absolute configuration of AM3 was determined in 1999 by extensive NMR analysis and degradation of the natural product, it was a daunting task because of the presence of numerous stereogenic centers on the acyclic carbon chain and the limited availability from natural sources. Thereafter, revisions of the absolute configurations at C2 and C51 were reported in 2008 and 2013, respectively. Reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Two examples of synthetic studies of karlotoxin 2 (KmTx2) were reported by Hamann group (the C42−C63 section) and Mohapatra group (the C29−C41 section) . We envisaged that the target compounds ( 1 a and 1 b ) would be synthesized through the assembly of three components via alkenyllitium‐aldehyde coupling of the B‐ring aldehydes ( 2 a and 2 b ) and alkenyllithiums derived from the A‐ring iodoolefins ( 3 a and 3 b ), followed by Julia‐Kocienski olefination with sulfone 4 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two examples of synthetic studies of karlotoxin 2 (KmTx2) were reported by Hamann group (the C42−C63 section) and Mohapatra group (the C29−C41 section) . We envisaged that the target compounds ( 1 a and 1 b ) would be synthesized through the assembly of three components via alkenyllitium‐aldehyde coupling of the B‐ring aldehydes ( 2 a and 2 b ) and alkenyllithiums derived from the A‐ring iodoolefins ( 3 a and 3 b ), followed by Julia‐Kocienski olefination with sulfone 4 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Having synthesized the A‐ring fragments, we moved on to the coupling reactions (Scheme ). The iodoolefin 3 a was treated with t ‐BuLi to generate alkenyllithium 15 a , which was coupled with the aldehyde 2 a (1.1 equivalents to 3 a ) to afford secondary alcohols 16 a (52% based on 3 a ) and 17 a (14%) as a mixture of diastereomers at C41 in a 3.7 : 1 ratio . Protection of the alcohol 16 a as TBS ether (81%) and removal of the PMB group of 18 a furnished primary alcohol 19 a (85%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, the J BCA is still the most powerful tool today for the assignment of the relative configurations of acyclic polyol structures, but it has an apparent defect. When the observed 3 J H,H and 2, 3 J C,H values appear in the medium range, it may result in the misassignment of stereochemistry, such as the originally proposed configuration of C51 in AM3 and that of C49 in KmTx2 . In this case, additional convincing evidence is required.…”
Section: Introductionmentioning
confidence: 97%
“…The absolute configuration of AM3 was first established by chemical degradation, the J ‐based configurational analysis ( J BCA), and modified Mosher's MTPA ester method in 1999 . Unfortunately, the originally reported stereochemistry has been revised three times with the last extensive revision in 2018 reconfirmed by total synthesis this year . Undoubtedly, the J BCA is still the most powerful tool today for the assignment of the relative configurations of acyclic polyol structures, but it has an apparent defect.…”
Section: Introductionmentioning
confidence: 99%